Online Marketing Web Analysis of a Real Estate Agency - Kvasnička, Jakub (2025)
The aim of this bachelor’s thesis is to analyse the online marketing activities of a selected real estate agency and to evaluate the performance of its website based on data collected through Google Analytics. The thesis examines how specific marketing channels influence website traffic and user behaviour, and highlights areas that can be improved in order to achieve more effective online presence. The theoretical section introduces key concepts of online marketing, digital analytics tools, and marketing models. The practical part includes user testing and a detailed analysis of data metrics, which together provide a comprehensive overview of the website’s performance. Based on these findings, the thesis gives recommendations for improving the overall online marketing activities of the real estate agency.